Open-Loop Control on the Efficiency of Quantum Battery With Reservoir Engineering - Borisenok, S. (Institute for Problems in Mechanical Engineering, Russian Academy of Sciences, 2025)
We discuss the case of a harmonic oscillator-based quantum battery strongly coupled to a highly nonMarkovian thermal reservoir via the quantum charger described by the Caldeira–Leggett model. The coupling between the reservoir and the battery serves as a control parameter for the system. We consider the system to stay in the strongly underdamped regime. Within the framework of the open-loop approach, we determine the optimal shape of control for the battery charging work and then restore the control coupling characteristics of QB in the Hamiltonian for the alternative cases of low and high temperatures. Ultimately, we discuss some possible ways to develop our model for the feedback algorithms. © 2025 Elsevier B.V., All rights reserved.
Keywords: Caldeira–Leggett Model; Open-Loop Control; Quantum Battery; Reservoir Engineering; Underdamped Regime